Novel self-assembling conjugates as vectors for agrochemical delivery - Pavani P. Nadiminti; Qingtao Liu; Lavanya K. Vanjari; Yao D. Dong; Ben J. Boyd; David M. Cahill (Journal of Nanobiotechnology, 2018)
Abstract Background Modern agricultural practises rely on surfactant-based spray applications to eliminate weeds in crops. The wide spread and indiscriminate use of surfactants may result in a number of deleterious effects that are not limited to impacts on the crop and surrounding farm eco-system but include effects on human health. To provide a safer alternative to the use of surfactant-based formulations, we have synthesised a novel, self-assembling herbicide conjugate for the delivery of a broad leaf herbicide, picloram. Results The synthesized self-assembling amphiphile–picloram (SAP) conjugate has three extending arms: a lipophilic lauryl chain, a hydrophilic polyethylene glycol chain and the amphiphobic agrochemical active picloram. We propose that the SAP conjugate maintains its colloidal stability by quickly transitioning between micellar and inverse micellar phases in hydrophilic and lipophilic environments respectively. The SAP conjugate provides the advantage of a phase structure that enables enhanced interaction with the hydrophobic epicuticular wax surface of the leaf. We have investigated the herbicidal efficiency of the SAP conjugate compared against that of commercial picloram formulations using the model plant Arabidopsis thaliana and found that when tested at agriculturally relevant doses between 0.58 and 11.70 mM a dose-dependent herbicidal effect with comparable kill rates was evident. Conclusion Though self-assembling drug carriers are not new to the pharmaceutical industry their use for the delivery of agrochemicals shows great promise but is largely unexplored. We have shown that SAP may be used as an alternative to current surfactant-based agrochemical formulations and has the potential to shift present practises towards a more sustainable approach.